Me the people how populism transforms democracy - Urbinati, Nadia 1955- (Harvard University Press, 2019)
Populism suddenly is everywhere, and everywhere misunderstood. Nadia Urbinati argues that populism should be regarded as government based on an unmediated relationship between the leader and those defined as the "good" or "right" people. Mingling history, theory, and current affairs, Urbinati illuminates populism’s tense relation to democracy